Concurrent pathogenic variants in SLC6A1/NOTCH1/PRIMPOL genes in a Chinese patient with myoclonic-atonic epilepsy, mild aortic valve stenosis and high myopia - Haiming Yuan; Qingming Wang; Yufeng Li; Shuangxi Cheng; Jianxin Liu; Yanhui Liu (BMC, 2020)
Abstract Background Pathogenic SLC6A1 variants have been reported in patients with myoclonic-atonic epilepsy (MAE). NOTCH1, encoding a member of the Notch family of proteins, is known to be associated with aortic valve disease. The PRIMPOL variant has only been identified in Chinese patients with high myopia. Exome sequencing analysis now allows the simultaneous detection of multiple genetic etiologies for patients with complicated clinical features. However, the presence of three Mendelian disorders in one patient supported by their respective pathogenic variants and clinical phenotypes is very rare. Case presentation Here, we report a 4-year-old Chinese boy who presented with MAE, delayed language, borderline intellectual disability (ID), mildly impaired social skills and attention deficit hyperactivity disorder (ADHD). He also had mild aortic valve stenosis and high myopia. Using whole-exome sequencing (WES), we identified three variants: (1) SLC6A1, NM_003042.4: c.881-883del (p.Phe294del), (2) NOTCH1, NM_017617.5:c.1100-2A > G and (3) PRIMPOL, NM_152683.4:c.265 T > G (p.Tyr89Asp). Parental Sanger sequencing confirmed that SLC6A1 and NOTCH1 variants were de novo, whereas the PRIMPOL variant was inherited from the father who also had high myopia. Furthermore, the PRIMPOL variant was absent from the genomes of the paternal grandparents, and thus was also a de novo event in the family. All three variants are classified as pathogenic. Conclusion The SLC6A1 variant could explain the features of MAE, delayed language, borderline ID, impaired social skills and ADHD in this patient, whereas the features of aortic valve stenosis and high myopia of the patient may be explained by variants in NOTCH1 and PRIMPOL, respectively. This case demonstrated the utility of exome sequencing in uncovering the multiple pathogenic variants in a patient with complicated phenotypes due to the blending of three Mendelian disorders.